Analisa Drainase Untuk Penanggulangan Banjir Menggunakan EPS SWMM (Studi Kasus : Perumahan Mutiara Witayu Kecamatan Rumbai Pekanbaru) - M Rizal Zarkani; Bambang Sujatmoko; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Flood is one of the negative effects that are often encountered during the rainy season. In addition to rain, flooding is also caused by tidal wave and poor management of drainage. Housing area of Mutiara Witayu located at Gotong Royong street Sri Meranti Village District of Rumbai Pekanbaru is an area that is prone to flooding so it is necessary to work on a solution that can cope with flooding. This study aimed to evaluate the capacity of drainage and determine the alternatives to address the problem of flooding. EPA SWMM application version 5.0 is used to evaluate the problems. The results showed that the application of EPA SWMM 5.0 quite reliable to evaluate the channel capacity in order to cope with the flooding. There are 4 simulations which were performed in this study. The simulation results of changing the slope of the channel is able to cope with the flood by 82,635%, simulation by changing the channel dimensions of 0,80,8 m, 1,01,0 m, and 1,01,2 m respectively can to cope with the flood by 89,295 %, 92,915% and 94,797%, while simulation by changing the dimension and slope can to cope with the flood by 100%. Simulations by operating the pump with 6 m3/s discharge is able to dispose the water that goes into the storage pool when the door is operated.Keywords: Flood, Drainage, EPA SWMM 5.0